Unprecedented Insights on Chemical and Biological Significance of Euphorbia cactus Growing in Saudi Arabia - Gadah A. Al-Hamoud; Omer I. Fantoukh; Musarat Amina; Fahd A. Nasr; Nawal M. Al Musayeib; Mohammad Z. Ahmed; Omar M. Noman; Reem E. Al-Sharidah; Fawaz Alasmari; Ali S. Alqahtani (Plants, 2022)
Euphorbia cactus Ehrenb ex Boiss. is a plant species reported from central Africa and the southern Arabian Peninsula, belonging to the family of Euphorbiaceae. The plant has ethnobotanical values and is well-known for its milky latex, which has been turned into medicine to treat various ailments. To the best of our knowledge, there have been no literature reports available on phytochemical constituents and antiproliferative mechanism of E. cactus. In the current study, the phytochemical investigation of E. cactus methanolic extract (ECME) resulted in the isolation and characterization of four secondary metabolites, which are reported for the first time from this plant species. In addition, the results of 1,1-diphenyl-2-picrylhydrazyl (DPPH•) and ferrous ion chelating (FIC) assays expressed maximum antioxidant activity by ECME and the isolated phytochemicals. Furthermore, ECME exerted a promising antiproliferative effect against different cancer cell lines, and the A549 lung cancer cells were the most sensitive with an IC50 value of 20 µg/mL. The antiproliferative action of ECME in A549 cells was associated with cell accumulation in the G2/M phase and an increase in early and late apoptosis. In addition, RT-PCR and western blot analysis revealed that ECME decreased the anti-apoptotic (Bcl-2) expression, while the expression of pro-apoptotic (Bax) and caspase-3 were increased. This study provides the first insight into the phytochemical constituents and the antiproliferative mechanism of ECME, implying that it could be exploited as a promising natural source for developing new cancer therapies. Further preclinical research is warranted to support the current results.